Determinan Sosial Kesehatan Terhadap Kepatuhan Pengobatan Dots Penderita Tb Paru - Kartikasari Masting; Muhammad Syafar; Andi Yusuf (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; pulmonary TB is an infectious disease caused by Mycobacterium tuberculosis. Transmission occurs when a smear-positive pulmonary TB patient coughs or sneezes and the patient accidentally spreads germs into the air in the form of phlegm splashes. The purpose of this study was to determine the existence of social determinants of health on the compliance of dots treatment with pulmonary tuberculosis patients. Method; This research uses a descriptive-analytic method by using the "Cross-Sectional" study approach method by taking a sample from a population and using a questionnaire as a data collection tool. The population in this study was a sample of 33 people. The data obtained were processed in the form of univariate bivariate and multivariate analysis with =0.05 using SPSS. Results; shows that the relationship between knowledge p = 0.02, family support p = 0.01, drug swallowing supervision p = 0.00. Conclusion; that there is a relationship between knowledge, family support, and supervision of drug ingestion on adherence to DOTs treatment of pulmonary TB patients